Nephroprotective effect of aqueous acetonic extract of Morus alba and its underlying mechanisms against glyphosate-induced toxicity - in vivo model - Rebai, Olfa; Fattouch, Sami; Amri, Mohamed (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Glyphosate, the active substance in Roundup®, is the most widely used pesticide in the world and may be present as a residue in derived foods and drinking water. Previous reports have confirmed that extracts from leaves of Morus alba exert many pharmacological activities. However, renoprotective effects of M. alba extract and its underling molecular mechanism is still unknown. Wistar rats (180-200 g) were used in this study (n=5-6). A control group received 0.2 ml normal saline intraperitoneally (i.p) once daily for two weeks. Control animals received standard diet. Treated groups received either polyphenolic extract (100 mg/kg,i.p) or glyphosate (100 mg/kg, i.p), or co-administration (extract μg ml−1 kg b.w. and glyphosate 100 mg kg−1 b.w, i.p), daily until the 15thday of treatment. Lactate deshydrogenase LDH, serum concentrations of blood urea, creatinine and nitric oxide were measured using standard coloromertic methods. Renal oxidative stress, evidenced by increased malondialdehyde (MDA) and protein carbonyl levels and decline in superoxide dismutase (SOD) activity, was significantly alleviated by mulberry leaves extract (MLE) administration. MLE also appears to be able to modulate altered biochemical parametres by maintaining free iron and Ca2 + homeostasis, and regulate the endogenous antioxidant enzymes system. It seems that concurrent use of the aqueous acetonic fraction of M. alba, rich in chlorogenic acid and its isomeres, can protect kidneys from glyphosate-induced nephrotoxicity. Overall, MLE may possess protective activity against glyphosate-induced toxicity, which may be attributed to chlorogenic acid and its isomers, the most abundant phenolic acids present in its extracts. Mulberry leaves are a source of phenolic compounds and can be a good start towards discovering a new chemical compound which may lead to a new drug. A mulberry extract supplement could serve as a candidate for developing a safe, and promising nutraceutical product for the management of nephrotoxicity.